High‐throughput synchrotron X‐ray diffraction for combinatorial phase mapping. (6th October 2014) - Gregoire, J. M.; Van Campen, D. G.; Miller, C. E.; Jones, R. J. R.; Suram, S. K.; Mehta, A.
<x xml:space="preserve">Abstract</x> Discovery of new materials drives the deployment of new technologies. Complex technological requirements demand precisely tailored material functionalities, and materials scientists are driven to search for these new materials in compositionally complex and often non‐equilibrium spaces containing three, four or more elements. The phase behavior of these high‐order composition spaces is mostly unknown and unexplored. High‐throughput methods can offer strategies for efficiently searching complex and multi‐dimensional material genomes for these much needed new materials and can also suggest a processing pathway for synthesizing them. However, high‐throughput structural characterization is still relatively under‐developed for rapid material discovery. Here, a synchrotron X‐ray diffraction and fluorescence experiment for rapid measurement of both X‐ray powder patterns and compositions for an array of samples in a material library is presented. The experiment is capable of measuring more than 5000 samples per day, as demonstrated by the acquisition of high‐quality powder patterns in a bismuth–vanadium–iron oxide composition library. A detailed discussion of the scattering geometry and its ability to be tailored for different material systems is provided, with specific attention given to the characterization of fiber textured thin films. The described prototype facility is capable of meeting the structural characterization needs for the first generation of high‐throughput material genomic searches.